Use of scrap tire rubber in place of SBS in modified asphalt as an environmentally correct alternative for Brazil - de Almeida Junior, Adao Francisco [UNESP]; Battistelle, Rosane Aparecida [UNESP]; Bezerra, Barbara Stolte [UNESP]; de Castro, Rosani [UNESP] (Elsevier B.V., 2012)
Reusing scrap tires has become a worldwide challenge, especially due to the great difficulty in finding ecologically and economically feasible ways to dispose of them. This has led to the creation of specific programs and legislation for reusing scrap tires. Research has shown that a certain percentage of scrap tire rubber can be added to asphalt compositions, and this has become a worldwide practice. This paper describes the properties of four asphalt compositions modified with scrap tire rubber (STR) prepared in the laboratory. These properties are then compared with those of asphalt modified with styrene butadiene styrene (SBS), a synthetic polymer and one of the most common modifiers, to verify the feasibility of using scrap tire rubber as a substitute for SBS. The scope of this study does not include an analysis of how STR affects end-of-life asphalt. The main findings indicate that STR is a potential substitute of SBS in paving material, and although it does not meet some of the standard specifications when compared with SBS, these issues can be overcome by proper care during storage and transportation. The substitution of SBS by STR also showed the potential for about 10% in expenditure savings. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Modified asphalt; Scrap tires; Rubber; Environment